The Sufian Symbol and its significance in Abd Allah Hamadi's Poetry - احمد بقار (College of Education for Women, 2019)
This research paper looks to put its hands on sufi symbols which are applied by the algerian poet د abdallah hammadi د in his poetical works . the symbols it relies on are : ( symbolisme of wine . symbolisme of light . symbolisme of night . sufisme and nature , femal symbols ) . From these symbols we try to show its range of ability to apply it , with trying to determine its meaningful , dimensions .